Type I interferon inhibitor anifrolumab in active systemic lupus erythematosus (TULIP-1): a randomised, controlled, phase 3 trial. (December 2019) - Furie, Richard A; Morand, Eric F; Bruce, Ian N; Manzi, Susan; Kalunian, Kenneth C; Vital, Edward M; Lawrence Ford, Theresa; Gupta, Ramesh; Hiepe, Falk; Santiago, Mittermayer; Brohawn, Philip Z; Berglind, Anna; et al.
Summary: Background: Type I interferons are involved in systemic lupus erythematosus (SLE) pathogenesis. In a phase 2 trial, anifrolumab, a human monoclonal antibody to type I interferon receptor subunit 1, suppressed interferon gene signatures and substantially reduced SLE disease activity. Here, we sought to confirm the efficacy of anifrolumab versus placebo in a phase 3 trial of adult patients with SLE and moderate-to-severe disease activity despite standard-of-care treatment. Methods: TULIP-1 was a double-blind, randomised, controlled, phase 3 trial done at 123 sites in 18 countries. Included patients were aged 18–70 years, with moderate-to-severe SLE, and ongoing stable treatment with either prednisone or equivalent, an antimalarial, azathioprine, mizoribine, mycophenolate mofetil or mycophenolic acid, or methotrexate. Patients were randomly assigned (2:1:2) to receive placebo, anifrolumab 150 mg, or anifrolumab 300 mg intravenously every 4 weeks for 48 weeks. Stable standard-of-care treatment continued except for mandatory attempts at oral corticosteroid tapering for patients receiving prednisone or equivalent of 10 mg/day or more at baseline. The primary outcome was the difference between the proportion of patients who achieved an SLE responder index-4 (SRI-4) response at week 52 with anifrolumab 300 mg versus with placebo. Key secondary outcomes were the difference between the anifrolumab 300 mg group and the placebo group in: proportion of patients in the interferon gene signature test—high subgroup who achieved SRI-4 at week 52; proportion of patients on 10 mg/day or more corticosteroids at baseline who achieved a sustained dose reduction to 7·5 mg/day or less from week 40 to 52; proportion of patients with a cutaneous lupus erythematosus disease area and severity index (CLASI) activity score of 10 or higher at baseline who achieved a 50% or more reduction in CLASI score by week 12; proportion of patients who achieved SRI-4 at week 24; and annualised flare rate through week 52. Other measures of disease activity were also assessed at week 52, including the British Isles Lupus Assessment Group-based composite lupus assessment (BICLA). Safety was also assessed. Efficacy and safety analyses were done in the population of patients who received at least one dose of study drug. This trial was registered at ClinicalTrials.gov (NCT02446912 ). Findings: Between June 9, 2015, and June 16, 2017, 457 patients were randomly assigned to the anifrolumab 300 mg group (n=180), the anifrolumab 150 mg group (n=93), or the placebo group (n=184). The proportion of patients at week 52 with an SRI-4 response was similar between anifrolumab 300 mg (65 [36%] of 180) and placebo (74 [40%] of 184; difference −4·2 [95% CI −14·2 to 5·8], p=0·41). Similarly, proportions of patients with an SRI-4 response at week 24, and at week 52 in patients in the interferon gene signature test—high subgroup, did not differ between the anifrolumab and placebo groups. In patients with baseline oral corticosteroids of at least 10 mg/day, sustained dose reduction to 7·5 mg/day or less was achieved by 42 (41%) of 103 patients in the anifrolumab 300 mg group and 33 (32%) of 102 patients in the placebo group (difference 8·9 [95% CI −4·1 to 21·9]). In patients with CLASI activity score of at least 10 at baseline, at least 50% reduction by week 12 was achieved by 24 (42%) of 58 patients in the anifrolumab 300 mg group and 14 (25%) of 54 in the placebo group (difference 17·0 [95% CI −0·3 to 34·3]). Annualised flare rates were 0·60 for anifrolumab and 0·72 for placebo (rate ratio 0·83 [95% CI 0·60 to 1·14]). BICLA response was achieved by 67 (37%) of 180 patients receiving anifrolumab 300 mg versus 49 (27%) of 184 receiving placebo (difference 10·1 [95% CI 0·6 to 19·7]). Anifrolumab's safety profile was similar to that observed in phase 2, with similar proportions of patients having a serious adverse event between groups (25 [14%] of 180 for anifrolumab 300 mg, ten [11%] of 93 for anifrolumab 150 mg, and 30 [16%] of 184 for placebo). Interpretation: The primary endpoint was not reached. However, several secondary endpoints, including reduction in oral corticosteroid dose, CLASI responses, and BICLA responses, suggest clinical benefit of anifrolumab compared with placebo. Conclusive evidence for the efficacy of anifrolumab awaits further phase 3 trial data. Despite the inherent limitations of a 1-year phase 3 study, such as incomplete knowledge of applicability to the general population and scarce detection of rare safety signals, in addition to complications from prespecified restricted medication rules, our results suggest that anifrolumab might have the potential to provide a treatment option for patients who have active SLE while receiving standard therapy. Funding: AstraZeneca.